Brachiocephalic Vein and Superior Vena Cava Reconstruction with a Superficial Femoral Vein Graft - Palacio,Andres M (2022)
Abstract Superior vena cava syndrome (SVCS) is an entity that has become more frequent due to the increasing use of indwelling central venous catheters. Surgical management is considered in patients with extensive venous thrombosis and when endovascular therapy is not feasible. The use of superficial femoral vein is an excellent technique for reconstruction of the brachiocephalic vein and superior vena cava (SVC) in cases with benign and malignant etiologies. We describe two cases of SVCS that were managed surgically at our institution with replacement of the SVC and brachiocephalic veins with a superficial femoral vein graft technique.